Few possible models for 19.9%efficient (JOURNAL OF ADVANCES IN PHYSICS, 2014)
: Device modeling and simulation studies of a CIGS thin film solar cell have been carried out using SCAPS 2902. A variety of graded band gap structures of efficiency around 19.9% are examined. The study shows that material saving models with efficiency Î· around 19.9% is possible